Proposed new interior design scheme of Persatuan Bulan Sabit Merah (PBSM) Kuala Lumpur for PBSM Malaysia at No.25 Jalan Sultan Ismail, 50250 Kuala Lumpur / Mohamad Hafiz Sapri - Sapri, Mohamad Hafiz (Faculty of Architecture, Planning and Surveying, 2011)
The final project of interior architecture for diploma is the manifestation to students understanding on process aspects on interior architecture that has been studied from the basic to presentation level of design proposal. The chosen product for this project is Malaysian Red Crescent (PBSM) Kuala Lumpur center at No.25,Jalan Sultan Ismail,50250,Kuala Lumpur. The purpose of this project is to be create a new design for ‘PBSM’ Kuala Lumpur center and to gift awareness to people about ‘PBSM’ jobs. It is also to provide a good design with an inspiration of creating a built environment that leads to functions and giving comfort to all interior scheme. ‘PBSM’ Kuala Lumpur center is a place to manage and control all activities and work although it is only state branch but it has own works to do. Examples of scope of work of ‘PBSM’ is to give first aid to anybody who need, ambulance services, youth development program and many more. The research method for this project is based on observation of a few social club and center which gift same services through differences of local and international . In conclusion, the new design for ‘PBSM’ Kuala Lumpur center will be run should have the characteristic and client’s needs besides the suitable concept to be shown. The design hopefully, will give benefits to all, either all the ‘PBSM’ member or nonmember.